2014
DOI: 10.1007/s00198-014-2748-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low intensity vibration on bone and muscle in rats with spinal cord injury

Abstract: The findings demonstrate an ability of LIV to improve selected biomarkers of bone turnover and gene expression and to reduce osteoclastogenesis. The study indicates a possibility that LIV initiated earlier after SCI and/or continued for a longer duration would increase bone mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 56 publications
2
47
1
Order By: Relevance
“…25 In an SCI animal model, however, the effects of WBV on bone remain unclear. Bramlett et al 26 reported that low-intensity vibration (LIV), which started on the 28th day after SCI and continued for 35 days, improved selected bone markers, but not BMD of the femur and tibia, in 3-month-old SCI rats. Bone damages were found within 3 weeks after SCI in 6-week-old rats 27 and were more severe in SCI rats than in ovariectomized or sciatic neurectomy rats at the age of 6 weeks.…”
Section: Osteoporosis Is a Well-known Complication Of Spinal Cord Injmentioning
confidence: 99%
See 4 more Smart Citations
“…25 In an SCI animal model, however, the effects of WBV on bone remain unclear. Bramlett et al 26 reported that low-intensity vibration (LIV), which started on the 28th day after SCI and continued for 35 days, improved selected bone markers, but not BMD of the femur and tibia, in 3-month-old SCI rats. Bone damages were found within 3 weeks after SCI in 6-week-old rats 27 and were more severe in SCI rats than in ovariectomized or sciatic neurectomy rats at the age of 6 weeks.…”
Section: Osteoporosis Is a Well-known Complication Of Spinal Cord Injmentioning
confidence: 99%
“…Bramlett et al 26 showed that LIV for 35 days does not alter BMD and trabecular architecture in the contusion SCI model rats aged 3 months. In chronic SCI patients, either, LIV was not effective in improving BMD and TBMS.…”
Section: Effects Of Vibration Stimulus On Bone In Sci Ratsmentioning
confidence: 99%
See 3 more Smart Citations